Acetylcholinesterases from Musca domestica and Drosophila melanogaster brain are linked to membranes by a glycophospholipid anchor sensitive to an endogenous phospholipase. - Fournier, D.; Berge, J.B.; Cardoso de Almeida, M.L.; Bordier, C. (Journal of Neurochemistry, 1988)
The sensitivity of acetylcholinesterases (AChEs) from Musca domestica and from Drosophila melanogaster to the phosphatidylinositol-specific phospholipase C from Bacillus cereus and to the glycosylphosphatidylinositol-specific phospholipase C from Trypanosoma brucei was investigated. B. cereus phospholipase C solubilizes membrane-bound AChE, and both phospholipases convert amphiphilic AChEs into hydrophilic forms of the enzyme. The lipases uncover an immunological determinant that is found on other glycosylphosphatidylinositol-anchored membrane proteins after the same treatment. This immunological determinant is also present on the native hydrophilic form of AChE. The polypeptide bearing the active site of the membrane-bound enzyme migrates faster during sodium dodecyl sulfate-polyacrylamide gel electrophoresis than the same polypeptide from the soluble enzyme. We conclude that AChE from insect brain is attached to membranes via a glycophospholipid anchor. This anchor is covalently linked to the polypeptide bearing the active esterase site of the enzyme and can be cleaved by an endogenous lipase.